2003
DOI: 10.1002/cncr.11410
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term results in elderly patients with differentiated thyroid carcinoma

Abstract: BACKGROUNDThe authors assessed the biologic behavior of differentiated thyroid carcinoma in patients age 70 years or older and evaluated factors that influenced long‐term survival.METHODSAmong 1448 patients with differentiated thyroid carcinoma who were treated at the authors' institution over the past 60 years, 111 patients were identified who were age 70 years or older at the time of their initial diagnosis (range, 70–93 years). The authors conducted a retrospective analysis of the outcome of these 111 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 23 publications
6
76
3
Order By: Relevance
“…However, other studies demonstrated that the risk of recurrence significantly increased in PTMC patients with CLNM (Chow et al, 2003). In addition, some investigators have showed that the operations for recurred lymph nodes in PTC increased the risk of postoperative complications (Vini et al, 2003) . Furthermore, CLND is helpful to assess the accurate staging of lymph node (Levin et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies demonstrated that the risk of recurrence significantly increased in PTMC patients with CLNM (Chow et al, 2003). In addition, some investigators have showed that the operations for recurred lymph nodes in PTC increased the risk of postoperative complications (Vini et al, 2003) . Furthermore, CLND is helpful to assess the accurate staging of lymph node (Levin et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Younger group were ,70 years of age. The cutoff of age groups is based on that was used in the previous studies (3,4). Their clinicopathologic and molecular features were analyzed.…”
Section: Patientsmentioning
confidence: 99%
“…The American Joint Committee on Cancer has defined a staging system for differentiated thyroid carcinoma according to age. Elderly patients who have a short life expectancy also present with poor prognostic factors including advanced stage, lymph node metastasis and distant metastasis, as compared with younger patients (3).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, few reports specifically analyze the behavior of thyroid cancer in the elderly. Vini et al [2003] studied the biological behavior in 111 patients with DTC, who were older than 70. The authors found that older age was an important risk factor for overall survival.…”
Section: The Age Factormentioning
confidence: 99%
“…Furthermore, investigators showed that the probability of survival changed significantly according to the decade in which the patient was treated. Thus, median survival improved from 4.7 years before 1970, to more than 10 years after 1990 [Vini et al, 2003]. J.…”
Section: The Age Factormentioning
confidence: 99%